New generation impact and vibration insulation based on high pressure force-network technology - Bek, Marko; Aulova, Alexandra; Oseli, Alen; Emri, Igor (Anali PAZU, 2022)
The article reviews the know-why and the know-how of an invention based on the patented dissipative granular high-pressure technology. It was found that by proper selection of damping material and hydrostatic pressure to which material is exposed during the loading, one can match material maximum damping properties with the frequency or rate of the applied loading. In this way one can fully utilize damping characteristics of the selected material and maximize the energy absorption properties of a damper. Using this unique potential of the dissipative granular high-pressure technology one can build ultimate damping elements that surpass the existing damping elements for sever orders of magnitude. Applications of such damping elements include for instance supports for industrial machines to damp vibrations, fundaments in building constructions to reduce susceptibility to earthquake damage and resonance, as well as trains and railway tracks to reduce vibration during travel, and to improve passive car safety in road transportation. This article reviews phenomenological description of the time-dependent response of polymeric material when excited by impact- or vibrational loading needed in development of the new generation impactand vibration isolation.
Keywords: effect of pressure; viscoelasticity; dissipative granular materials; damping elements; thermoplastic polyurethane